2017
DOI: 10.1116/1.4982223
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of aqueous ammonium sulfide on SiGe 25%

Abstract: SiGe 25% substrates were treated with aqueous solutions of ammonium sulfide with and without added acid to understand the adsorption of sulfur on the surface. X-ray photoelectron spectroscopy showed no sulfide layer was deposited from aqueous (NH 4 ) 2 S alone and instead both Si and Ge oxides formed during immersion in the sulfur solution. The addition of hydrofluoric and hydrochloric acids dropped the pH from 10 to 8 and deposited sulfides, yet increased the oxide coverage on the surface and preferentially f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…When halogen acids are added to the sulfur solution, a mixture of sulfur and oxide is detected with XPS. We also reported that interface defects decreased with increased sulfur and oxide coverage (8). This study reports on the chemical and electrical stability of these surfaces in air after treatment with ammonium sulfide.…”
Section: Introductionmentioning
confidence: 68%
“…When halogen acids are added to the sulfur solution, a mixture of sulfur and oxide is detected with XPS. We also reported that interface defects decreased with increased sulfur and oxide coverage (8). This study reports on the chemical and electrical stability of these surfaces in air after treatment with ammonium sulfide.…”
Section: Introductionmentioning
confidence: 68%
“…The effect of chemical treatment on ML WSe 2 was probed after dipping the as-prepared ML WSe 2 sample in a 20% (NH 4 ) 2 S­(aq) solution (source: Sigma-Aldrich; 98% purity). , As shown in Figure a, the dissociation of (NH 4 ) 2 S in H 2 O solution is expected to result in the generation of SH and H 2 S species as per the following chemical reactions: , As shown in previous reports, the (NH 4 ) 2 S molecules are readily dissociated into molecular species such as NH 3 , SH, and H 2 S in H 2 O solution. Thus, these dissociated molecular species, including NH 3 , SH, H 2 S, etc.…”
Section: Resultsmentioning
confidence: 93%
“…The effect of chemical treatment on ML WSe 2 was probed after dipping the as-prepared ML WSe 2 sample in a 20% (NH 4 ) 2 S(aq) solution (source: Sigma-Aldrich; 98% purity). 35,36 As shown in Figure 2a, the dissociation of (NH 4 ) 2 S in H 2 O solution is expected to result in the generation of SH and H 2 S species as per the following chemical reactions: 50,51 isopropyl alcohol (IPA) to remove unintentional contaminants such as hydrocarbons, following which the samples were airdried.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when treating the sample with high concentration (NH 4 ) 2 S solution, as in this case, the polished sample surface was re‐oxidised by S 2 O 3 2− and lead to an increase of leakage current. The oxidation of the surface in concentrated sulfur solution was also observed from an XPS measurement study on SiGe, where it was proposed that sulfite and thiosulfate adsorb onto the surface and promote surface oxidation [11 ].…”
Section: Resultsmentioning
confidence: 99%
“…where it was proposed that sulfite and thiosulfate adsorb onto the surface and promote surface oxidation. [23] Besides HSions, H2S gas is another sulfide that contributes to the surface passivation. Since aqueous HSis not as effective as we expected, we surmised that the increase of H2S gas may enhance the effect of sulfur passivation.…”
Section: Results Discussionmentioning
confidence: 99%